The Reluctant Satirist: Theodor Haecker and the Dizzying Swindle of Nazism. (2nd January 2017) - Tomko, Helena M.
Abstract : Cultural critic and philosopher Theodor Haecker was arrested in 1933 in relation to an anti-Nazi essay he had published in 1932. This article tells the story of Haecker's essay, which satirizes the swastika as the dizzying symbol of political deception and dehumanization. After converting to Catholicism, Haecker had distanced himself from the mode of satire he had admired in Karl Kraus's writing. His brief return to satire in 1932 represents an aesthetic concession to moral and political urgency. Haecker describes the ideological duping of Germany as a collective dizzying of human experience and civic life. Haecker's essay, with its gestures towards dialogic discourse and its movement into monologic satire, sets the tone for his theory and practice of inner emigration/exile after 1933.